Open Osteotomy of ulna as a Model For Fracture Healing Studies in Rabbits. - Aljumaily, Mahmood A. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Bone healing of fractures is still an open field for research due to its biological complexity. Adequately adapted experimental model is essential for understanding the factorsinfluencing the biological process of bone healing. Rabbits provide a good animal model for bone healing studies; its bone had Haversian system similar to human.Material and Methods: Six young locally breaded New Zeeland male rabbits were used in this study, the study conducted in animal house in college of medicine at November and December 2009. Surgical fracture (osteotomy) induced operatively in right ulna under general anesthesia by a hand saw. At the end of fifth weeks, the animals' scarified and the specimens taken for radiological, computerized tomography (CT) scan densimetry and histological examination carried out for bone healing in site of osteotomyResults: All bone osteotomy united at end of fifth weeks macroscopically and radiologically. There was no significant difference in serum calcium, serum phosphate, and serum alkalinephosphatase preoperatively and at end of fifth weeks. The callus density was measured in site of osteotomy by CT scan densimetry and its mean was 302 ± 142. The histological examination of the bone at site of osteotomy show healing with woven bone predominantly with some lamellar bone and cartilage.Conclusion: The present study demonstrated that the ulnar osteotomy without use of external splintage or internal fixation model is a new, easy to perform and can be used as a model forfractures healing studies.